Persentase Pediculosis capitis pada Anak Usia 9-12 Tahun di RW XI Kampung Gampingan Kota Yogyakarta - Nurlaili Farida Muhajir; Desto Arisandi; Yuliana Prasetyaningsih (LPPM STIKES Guna Bangsa, 2015)
Background : Pediculosis capitis disease can be found all over the world without the restrictions of age, gender, race, economic status, and social status. Pediculosis capitis mainly affects young children and quickly spread in a dense environment such as dorm, orphanages, large cities and densely populated elementary school with bad hygiene, such behavior is rarely clean the hair. Factors that can help spread Pediculus humanus capitis infestation is socio-economic factors, level of knowledge, personal hygiene, environment, and individual characteristics (age, hair length, and hair type). Methods : This was descriptive study. The population in this study was children who were stayed in kampung Gampingan kota Yoyakarta. Sample was taken by purposive sampling with criteria of inclusion and exclusion. The instrument used laboratory examination about Pediculus humanus capitis with direct examination. Analysis of data used univariate analysis. Result & Conclusion : Pediculosis capitis children who have age 9-12 years in Kampung Gampingan RW XI Yogyakarta was 86.84%.